Causes of Hospitalization of Pregnant Women in Delivery Unit of Ayatollah Mosavi Hospital in Zanjan - Fateme Saremi; Shamsi Taran; Azam Malekia (Zanjan University of Medical Sciences and Health Services, 2012)
Background and Objectives: Health status, lifestyle and previous history of pregnancies significantly affect pregnancy outcome however, many adverse pregnancy outcomes are preventable. This study aimed to investigate causes of hospitalization of pregnant women in delivery unit of Zanjan Ayatollah Mosavi hospital. Material and Methods: In this cross-sectional study, the causes of hospitalization of 4830 women with gestational ages more than 20 weeks were investigated during 2009-2010. Data were collected using a check list including patientschr('39') chief complaint, women's demographic characteristics and delivery history. Data were analyzed using descriptive test, chi square, and t-test in a confidence level of 95 %. Results: From 4830 hospitalized women, 1278 were hospitalized due to obstetrics complications. The mean age of women was 26.52±6.26 year. The mean gestational age was 264.24±21.40 days. The most common causes of hospitalization were rupture of amniotic membranes (49.1%), preterm labor (29.3%), meconium staining (15.5%), and hypertension (11.8%). The rate of caesarian section, male baby, APGAR score lower than six in the 1st and 5th minutes of delivery, hypertension, and twin pregnancies were high in preterm labors. Meconium staining and rupture of amniotic membranes were common in term and post term deliveries. Conclusion: Findings showed that the most common causes of hospitalization were rupture of amniotic membranes and preterm labor. It is necessary to conduct more research on the causes of these complications